Working memory as separable subsystems: A study with Portuguese primary school children - Campos, I. S.; Almeida, L. S.; Ferreira, A. I.; Martinez, L. F. (The Spanish Journal of Psychology, 2013)
Although much research has been done to study the working memory structure in children in their first school years, the relation of cognitive constructs involved in this process remains uncertain. In particular, it is unclear whether working memory is a domain general construct that coordinates separate codes of verbal and visuospatial storage or whether it is a domain-specific construct with distinct resources of verbal and visuospatial information. This paper investigates the structure of working memory, by using the Working Memory Test Battery for Children (WMTB-C) and by doing confirmatory factor analyses (CFAs) on a sample of Portuguese children (n = 103) between 8 and 9 years of age. The results of the confirmatory factor analyses that provide the best fit of the data correspond to the model that includes Central Executive and Visuospatial Sketchpad in the same factor, co-varying with a Phonological Loop factor. Moreover, the traditional working memory tripartite structure – based on the Baddeley and Hitch Model – revealed good fit to the data.